Stress as Etiological Factor in Diseases of Mandibular Joint - V. Machoň; J. Paska (Czech Dental Chamber, 2007)
The authors investigated the influence of stress in intraarticular lesions of mandibular joint (discopathy, arthritis, arthrosis). In the group of 100 patients, a higher stress load was diagnosed in 40% of patients while 32.5% of patients suffered from discopathy and 45% patients from arthritis and osteoporosis. As far as the role of occupation in discopathy, the most frequently affected patients were those working in services (shop assistants, hairdressers) in 30% and retired individuals in 26.6%.Stress belongs to very frequent etiological factors and an indispensable part in the therapy of mandibular joint diseases is therefore psychotherapeutic approach, adequate pharmacotherapy and nonspecific psychotherapy.